Effects of Solvent to Feed Ratio and Microwave Power on Extraction of Essential Oil from Red Guava Leaves (Psidium guajava l.) Using Microwave Hydro Distillation Method - Febrian Lourenso Hangkaya; Jariyah; Sri Djajati; Anugerah Dany Priyanto (International Journal of Eco-Innovation in Science and Engineering, 2020)
Essential oils are typically hydrophobic liquid mixture of natural products containingoil, volatile, and aromatic compounds extracted from plant species. This experiment was used microwave hydro distillation as extraction method to obtain the essential oils due to its efficiency. The purpose of both treatments used to increase total yield of essential oil from red guava leaves. Completely randomized design was used as experimental design with two variables and run in triplicate. The first variable is solvent to feed ratio (4:1, 5:1, 6:1, 7:1) and the second variable is microwave power (300W and 450W). The results showed that the ratio of solvent to feed (7:1) and microwave power (450W) has the highest yield and best quality of essential oils. The best variable has some parameters, particularly yield of 1.24%, refractive index of 1.49, and density of 0.78 g/ml. Analysis of essential oil profile has some abundance compounds, namely naphtalene or β-seline at 24.45%, neointermedeol at 17.97%, and caryophyllene at 16.04%. Moreover, the IC50 value has an antioxidant activity of 41.95 ppm.